Randomized clinical trial of the safety and immunogenicity of the Tdap vaccine in pregnant Mexican women - Jesús Zacarías Villarreal Pérez; José Manuel Ramírez Aranda; Manuel de la O Cavazos; Michelle de J. Zamudio Osuna; José Perales Dávila; María Romelia Ballesteros Elizondo; Marco Vinicio Gómez Meza; Francisco Javier García Elizondo; Azucena M. Rodríguez González (Taylor & Francis Group, 2017)
Immunization with the tetanus, diphtheria, and pertussis (Tdap) vaccine raises controversies on immunogenicity and possible antibody interference. We performed an experimental, double-blind, parallel group controlled clinical trial to evaluate the safety and immunogenicity of the Tdap vaccine in 204 pregnant women and their children and to determine its interference in antibody production. Pregnant women 18 to 38 y of age with 12 to 24 weeks gestation, a low obstetric risk, and without serious disease were randomly selected. The experimental group received 0.5 mL IM of Tdap and the control group normal saline. Six blood samples were drawn before and after solution application, and from the umbilical cord of the infants and at 2, 4, and 6 months of age. Pertactin and Pertussis toxin antibodies and possible interference of maternal antibodies with the vaccine were determined. In the experimental group, antibodies against Bordetella pertussis pertactin (anti-PRN) (112 E/mL 95% CI 89.9-139.9) and antibodies against pertussis toxin (anti-PT) (24.0 E/mL, 95% CI 18.3-31.4) were elevated in the mother before vaccination. These were higher in the umbilical cord and descended in the infant at 2 months (71.4 (95% CI 56.8-89.7 and 10.9; 95% CI 8.7-13.7, respectively). Anti-PT showed a delay in production. Tdap safety was confirmed with only mild local pain at 24 and 48 hours. Anti-PRN and anti-PT antibodies in the infant descend at 2 months of age. There is a delay in anti-PT in children of immunized mothers. Further studies are needed to elucidate its clinical significance.